Isolation and Partial Chemical Characterization of the Spore Appendages of Clostridium taeniosporum - Yolton, Diane P. (1972)
The spore appendages of Clostridium taeniosporum NI were removed from the spores by sonic treatment and were isolated by using discontinuous sucrose gradients. The amino acid composition of the appendages, which are elaborations of the spore coat, was similar to but not identical with the amino acid composition of the coats. Approximately 80% of the appendage dry weight was composed of 17 common amino acids, whereas 68% of the spore coat dry weight was amino acids. Mole ratios of the amino acids differed between the appendages and spore coats. The appendages contained neither diaminopimelic acid nor hydroxyproline. Glucosamine was an abundant constituent but muramic acid was absent. Approximately 10% of appendage dry weight consisted of three sugars, one of which was glucose. Phosphorus content was high and dipicolinic acid was absent. Appendage fine structure was not affected by common buffers, dilute acids and bases, hydrogen bond-breaking agents, certain proteolytic enzymes, or lysozyme.